A retained iatrogenic foreign body in nasal cavity presenting with a hard palatal fistula - Chandni Shankar; Karoon Agrawal (Wolters Kluwer Medknow Publications, 2015)
A 30-year-old male presented with a hard palate fistula. He had a history of faciomaxillary injury 8 months back. He had nasal regurgitation after the injury. He had severe halitosis at the time of presentation. A large foam piece was removed through the fistula under general anesthesia. There was a lack of documentation regarding the placement of foam piece as a nasal pack during initial treatment. A need of good documentation of the removal of the foreign body is emphasized.